Urban Development in the Heritage Cities, Wadi Mazab - Zanati, D (KnE Engineering, 2018)
This research paper, which was prepared under the patronage of Prince Sultan Bin Salman’s Chair for Urban Heritage, the problem of housing in heritage cities and how to adopt the urban heritage as a reference for the development of housing models with environmental specifications, Economic and social sustainability based on the analysis of local traditional architecture and the extraction of principles and characteristics. This character is to be employed and adopted in new urban models. The aim of this paper is to draw on a distinctive architectural philosophy organization and structure of the field and social and social pressures contributing to the needs of the population and the sustainability of the idea of Al-Amrani This is a sample of the housing models for the success factors and the reasons behind the future housing projects. At the beginning of this research, we relied on the diagnosis and development of traditional buildings in the old palaces as housing models which has managed to provide, over a thousand years, adequate accommodation for the desert climate and environment-friendly. The project of the new palace of Tennmeren and Kastravaltal are reviewed, which are considered the most important models of successful housing in the valley of Mazab which will contribute to the formulation of new concepts to maintain our urban patterns and continuity in light of the changes of the age. In order to avoid the disincentives to the success of these projects, we reviewed the Palace of Hamriyat to identify the most important shortcomings and to identify the most important reasons In conclusion, we concluded with a number of recommendations, based entirely on the need to adopt the principles of conventional housing.